2021
DOI: 10.1136/bmj.m4786
|View full text |Cite
|
Sign up to set email alerts
|

Electronic health record alerts for acute kidney injury: multicenter, randomized clinical trial

Abstract: Objective To determine whether electronic health record alerts for acute kidney injury would improve patient outcomes of mortality, dialysis, and progression of acute kidney injury. Design Double blinded, multicenter, parallel, randomized controlled trial. Setting Six hospitals (four teaching and two non-teaching) in the Yale New Haven Health System in Connecticut and Rhode Island, US, ranging from small com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
138
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 29 publications
4
138
0
Order By: Relevance
“…It will be crucial to monitor for unanticipated untoward effects, given the potential harm that can be induced by CDS. 17 , 67 …”
Section: Discussionmentioning
confidence: 99%
“…It will be crucial to monitor for unanticipated untoward effects, given the potential harm that can be induced by CDS. 17 , 67 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the impact of AKI alerts were performed on hospitalized patients and reported variable impacts on clinical outcomes. [8][9][10][11][12][13][15][16][17] Aiyegbushi et al performed a study on hospitalized patients and showed that an AKI alert was associated with a dramatic reduction in the repeat testing interval for creatinine. 15 However, Wilson et al in a single-center, randomized controlled trial of more than 23,000 hospitalized adult patients found that an AKI alert had no impact on the clinical outcomes of peak creatinine concentration, initiation of RRT, or death during the current hospital admission or within 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Most reports of electronic notification of AKI have focused on in-hospital AKI events. [11][12][13] However, early identification and management of AKI in the outpatient setting may prevent worsening AKI and the associated consequences of severe and/or prolonged AKI. Kidney function in the 72-hour period immediately following AKI in hospitalized patients is associated with specific clinical outcomes: the development or progression of CKD, initiation of long-term dialysis, or death from any cause within a median follow-up of approximately 4.7 years.…”
Section: Introductionmentioning
confidence: 99%
“…A 2-year follow-up study on an additional 337,433 patients demonstrated sustained decrease in mortality rate and length of stay, as well as a significant decrease in the use of nephrotoxic agents (39). More recently, Wilson et al looked at e-alerts for AKI in 6,030 patients in a double blinded, parallel, randomized controlled trial across six centers (34). In the electronic health record alerts for acute kidney injury (ELAIA-1) study, they found that patients randomized to alerts were more likely to receive intravenous fluids, get a urinalysis or repeat SCr measured, and have documentation of AKI.…”
Section: Use Of Aki Alerts In Adultsmentioning
confidence: 99%
“…Currently, care bundles include general common sense measures such as optimal fluid management, medication review, and urinalyses (Table 1). However, as seen in the ELAIA-1 study (34), care bundles that do not provide patient specific recommendations may not be helpful, and have the potential to cause more harm. Additional research is needed on this aspect of CDSS.…”
Section: Interventions Associated With Alertmentioning
confidence: 99%